PEMODELAN HIDROLOGI DENGAN HEC-HMS DI SUB-DAS KARANGMUMUS SAMARINDA - Rachmad Mulyadi; Yohanes Budi Sulistioadi; Ali Suhardiman (Fakultas Kehutanan Universitas Mulawarman, 2020)
Hydrological Modeling with HEC-HMS in the Karangmumus Sub-watershed Samarinda. The HEC-HMS is used to develop a model of water flow in the Karangmumus which can be used as an alternative for flooding problem. The purpose of this study is to determine the amount of flow discharge generated from rainfall that enters the Karangmumus using the HEC-HMS and to determine the effect of rain parameters on the HEC-HMS to make an hydrological model simulation.For simulation using daily rainfall and water level data, curve number, percentage of watertight, amount of initial absorption and the time needed to reach the peak discharge in the sub-watersheds obtained from the river model created. The highest rainfall Karangmumus Sub-watershed that is 84,4 mm produces a discharge of 211 m3/sec and at the lowest rainfall of 1,05 mm produces a discharge of 3,4 m3/sec. Hydrological modeling of the simulation results has the same hydrograph with the rainfall data but not the discharge data calculated with the rating curve. The validation of observing the debit data of the efficiency value (NSE) <0,36 which means that the data used are not satisfactory or invalid.